Tied Up In Knots - Sommer, Carl, 1930-; Budwine, Greg (Houston, TX : Advance Pub., 1997)
Until they see their two stubborn mules finally resolve a behavior problem, Benny and Sally refuse to believe that sharing could bring happiness.
Keywords: Behavior -- Fiction; Mules -- Fiction